A halide electrolyte material, and a method of making and using the same

CN123018114APending Publication Date: 2026-10-30ZHEJIANG INTELLIGENT TRANSPORTATION TECHNOLOGY INNOVATION CENTER +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611501638.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-24
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

然而,现有卤化物电解质仍普遍存在电化学窗口有限、离子电导率和空气稳定性有待进一步提高等问题

Benefits of technology

[0010]本发明提供一种用电设备,续航、充放电速度及安全性有所提升。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123018114A_ABST
    Figure CN123018114A_ABST
Patent Text Reader

Abstract

The application provides a halide electrolyte material and a preparation method and application thereof. The material comprises: (1-x)Li a Q·xLi2O·yTaCl5·zM b Q c ; wherein, 0
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of energy storage technology, and in particular to a halide electrolyte material, its preparation method, and its application. Background Technology

[0002] With the rapid development of new energy vehicles, large-scale energy storage, and high-end electronic devices, lithium-ion batteries are facing higher demands for energy density, safety, and cycle life. Compared to traditional liquid lithium-ion batteries, all-solid-state batteries use solid electrolytes instead of flammable and volatile organic liquid electrolytes, offering higher intrinsic safety, a wider operating temperature range, and the potential for compatibility with high-capacity negative electrodes and high-voltage positive electrodes. They are considered an important development direction for next-generation high-performance energy storage technology. As the core medium for lithium-ion transport in all-solid-state batteries, the solid electrolyte directly affects the battery's ion transport efficiency, interface stability, rate performance, and cycle life, making it a key material determining the overall performance of all-solid-state batteries.

[0003] Currently, solid-state electrolytes mainly include oxide electrolytes, sulfide electrolytes, polymer electrolytes, and halide electrolytes. Among them, halide electrolytes, which have been developed in recent years, combine high ionic conductivity and good cathode compatibility, and have become an important research direction in the field of all-solid-state batteries. However, existing halide electrolytes still generally suffer from problems such as limited electrochemical window, and the need for further improvement in ionic conductivity and air stability. These problems limit the full utilization of the capacity of the active cathode material, resulting in limited ion transport at high current densities and capacity decay during cycling, making it difficult to meet the application requirements of high-power, high-energy-density all-solid-state batteries.

[0004] Therefore, developing a halide solid electrolyte material with high ionic conductivity, wide electrochemical window, and excellent air stability to further improve the overall performance of all-solid-state batteries has become an urgent technical problem to be solved in this field. Summary of the Invention

[0005] This invention provides a halide electrolyte material with high ionic conductivity, a wide electrochemical window, and excellent air stability.

[0006] This invention provides a method for preparing a halide electrolyte material, the material obtained by this method having high ionic conductivity, a wide electrochemical window, and excellent air stability.

[0007] This invention provides an electrolyte membrane with high ionic conductivity, a wide electrochemical window, and excellent air stability.

[0008] This invention provides an electrode with high ionic conductivity, a wide electrochemical window, and excellent air stability.

[0009] This invention provides a battery with improved energy density, rate performance, and safety.

[0010] This invention provides an electrical device with improved battery life, charging and discharging speed, and safety.

[0011] In a first aspect, the present invention provides a halide electrolyte material, comprising:

[0012] (1-x)Li a Q·xLi2O·yTaCl5·zM b Q c ; among which, 0 <x≤1,0.9≤y≤1.2,0<z≤0.5,1≤a≤3,1≤b≤5,3≤c≤6;

[0013] M is at least one of Ta, Nb, W, Al, and Ga, and Q is at least one of F, Cl, Br, I, S, and N.

[0014] In one possible embodiment, the material as described above includes a Cmc21 crystal phase and an Fm-3m crystal phase, wherein the mass fraction of the Cmc21 crystal phase and the Fm-3m crystal phase is greater than 90% of all crystal phases.

[0015] In one possible embodiment, the electrolyte material, as described above, is a rod-shaped particle with a diameter of 1-3 μm and a length of 5-20 μm.

[0016] In a second aspect, the present invention provides a method for preparing an electrolyte material according to any one of the first aspects of the present invention, comprising the following steps:

[0017] A raw material system including lithium source, tantalum source, M source and oxygen source is subjected to a first-stage annealing treatment to obtain a halide electrolyte precursor;

[0018] The halide electrolyte precursor is subjected to a two-stage annealing process to obtain the halide electrolyte material.

[0019] The first-stage annealing process is carried out at a temperature of 120-230℃ for 2-8 hours; the second-stage annealing process is carried out at a temperature of 230-260℃ for 3-10 hours.

[0020] In one possible embodiment, as described above, the first-stage annealing process is performed in an inert gas atmosphere, which includes at least one of nitrogen and argon.

[0021] The two-stage annealing process is carried out in a mixed gas atmosphere, which includes at least one of nitrogen and argon, and the total volume fraction of argon and nitrogen is 90-95%, with the remainder being at least one of oxygen and ozone.

[0022] In one possible embodiment, as described above, the lithium source is at least one of LiCl, LiOH, Li2O, Li2O2, LiCl·H2O, Li2S, and Li3N.

[0023] In one possible embodiment, as described above, the M source is at least one selected from AlCl3, GaCl3, WCl5, WCl6, NbCl5, and TaCl5.

[0024] In one possible embodiment, as described above, the oxygen source is at least one of Li2O, Li2O2, LiCl·H2O, AlCl3·6H2O, and Al(OH)3.

[0025] In one possible embodiment, as described above, before the first stage of annealing, the raw material system is subjected to a first premixing treatment, and before the second stage of annealing, the halide electrolyte precursor is subjected to a second premixing treatment.

[0026] Thirdly, the present invention provides an electrolyte membrane comprising the electrolyte material described in any one of the first aspects of the present invention, or the electrolyte material obtained by any one of the methods described in the second aspect of the present invention.

[0027] Fourthly, the present invention provides an electrode comprising the electrolyte material described in any one of the first aspects of the present invention, or the electrolyte material obtained by any one of the methods described in the second aspect of the present invention.

[0028] Fifthly, the present invention provides a battery comprising the electrolyte membrane described in the third aspect of the present invention, or the electrode sheet described in the fourth aspect of the present invention.

[0029] In one possible embodiment, the battery is a solid-state battery, the solid-state battery including a solid electrolyte layer, the solid electrolyte material in the solid electrolyte layer including the electrolyte material according to any one of the first aspects of the present invention, or the electrolyte material obtained by any one of the second aspects of the present invention.

[0030] In a sixth aspect, the present invention provides an electrical device including the battery described in the fifth aspect of the present invention.

[0031] This invention provides a halide electrolyte material, its preparation method, and its applications. By constructing a multi-component halide electrolyte system and introducing an appropriate amount of oxygen using Li₂O, the halide crystal structure is regulated, optimizing the local coordination environment and migration channels of lithium ions. Simultaneously, the nitrogen (M) and phosphorus (Q) elements synergistically regulate the lattice structure and chemical bonding environment of the material, improving the electrolyte's oxidation resistance under high-voltage conditions and thus broadening the electrochemical stability window. Furthermore, the combined effect of oxygen and high-valence M elements enhances the material's tolerance to humid air environments and reduces its decomposition tendency in humid air. Through the synergistic optimization of the composition and proportion of each component, this invention achieves a balance of high ionic conductivity, a wide electrochemical window, and excellent air stability, meeting the application requirements of high-performance battery materials. Attached Figure Description

[0032] The accompanying drawings, which are incorporated in and form part of this specification, illustrate embodiments consistent with the invention and, together with the description, serve to explain the principles of the invention.

[0033] Figure 1 XRD contrast spectrum provided by this invention;

[0034] Figure 2 The SEM spectrum provided in Embodiment 9 of the present invention;

[0035] Figure 3 The SEM spectrum provided in Embodiment 21 of the present invention;

[0036] Figure 4 The SEM spectrum provided in Comparative Example 1 of this invention is shown.

[0037] The accompanying drawings have illustrated specific embodiments of the invention, which will be described in more detail below. These drawings and descriptions are not intended to limit the scope of the invention in any way, but rather to illustrate the concept of the invention to those skilled in the art through reference to particular embodiments. Detailed Implementation

[0038] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions of this invention will be clearly and completely described below in conjunction with the embodiments of this invention. Obviously, the described embodiments are only some embodiments of this invention, not all embodiments. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention.

[0039] With the rapid development of new energy vehicles, large-scale energy storage, and portable electronic devices, all-solid-state batteries have become an important development direction for the next generation of energy storage technology due to their advantages such as high safety, high energy density, and wide operating temperature range.

[0040] Solid-state electrolytes, as the core functional materials for lithium-ion transport in all-solid-state batteries, directly affect the battery's rate performance, cycle life, and practical application value due to their ionic conductivity, electrochemical stability, and environmental stability. Currently, halide electrolytes, possessing both high ionic conductivity and good cathode compatibility, have attracted widespread attention in recent years. However, existing halide electrolytes still suffer from problems such as the need for further improvement in ionic conductivity, limited electrochemical window, insufficient air stability, and complex preparation processes, making it difficult to simultaneously meet the demands of high performance and industrial applications.

[0041] Based on this, the present invention starts from the synergistic regulation of the composition system of halide electrolytes. By designing the material composition and structure as a whole, it achieves a synergistic improvement in lithium-ion transport capacity, electrochemical stability and environmental stability, thereby providing a new technical approach for obtaining halide solid electrolytes with high ionic conductivity, wide electrochemical window and excellent air stability.

[0042] In a first aspect, the present invention provides a halide electrolyte material, comprising:

[0043] (1-x)Li a Q·xLi2O·yTaCl5·zM b Q c ; among which, 0 <x≤1,0.9≤y≤1.2,0<z≤0.5,1≤a≤3,1≤b≤5,3≤c≤6;

[0044] M is at least one of Ta, Nb, W, Al, and Ga, and Q is at least one of F, Cl, Br, I, S, and N.

[0045] In this invention, Li a Q, as a source of lithium and halogens, provides the charge-carrying ions required for lithium-ion transport in the material and participates in the formation of the halide crystal framework, providing a basic channel for lithium-ion migration. Li₂O can replenish oxygen in the system, regulate the local coordination environment and lattice structure of the material; at the same time, it optimizes the local migration environment of lithium ions, which helps to reduce the lithium-ion migration barrier, optimize the lithium-ion migration efficiency, enhance the stability of the crystal structure, and improve the material's tolerance to humid air environments.

[0046] TaCl5, as the host lattice building block, together with lithium and halogen elements, forms a stable halide electrolyte host structure, providing a continuous ion transport framework for the material. Elements such as Ta, Nb, W, Al, and Ga from the M source, after entering the host lattice, regulate the local coordination environment and lattice parameters, optimizing crystal structure integrity and improving the electrochemical stability of the material under high voltage conditions. Simultaneously, different Q elements, including F, Cl, Br, I, S, and N, can further modulate the chemical bonding environment and local structure, enabling the material to possess both high ion transport capacity and a wide electrochemical window.

[0047] Furthermore, by adjusting the composition ratios of x, y, and z, the composition ratios of Li₂O, TaCl₅, and M can be adjusted. b Q c The synergistic effect between them ensures the stable formation of the main crystal phase while taking into account lithium ion migration ability, crystal structure stability and interface stability, so that the resulting halide electrolyte has high ionic conductivity, wide electrochemical window and excellent air stability, which meets the application requirements of high-performance solid electrolyte materials.

[0048] In one possible embodiment, the material as described above includes the Cmc21 and Fm-3m crystal phases, wherein the mass fraction of the Cmc21 and Fm-3m crystal phases is greater than 90% of all crystal phases.

[0049] This embodiment further optimizes the crystal structure of the halide electrolyte, resulting in a material with Cmc21 and Fm-3m crystal phases. In the XRD pattern, the 2θ diffraction peaks at approximately 14°±0.5°, 20°±0.5°, 25°±0.5°, 28.5°±0.5°, 31.5°±0.5°, 43°±0.5°, and 46.5°±0.5° correspond to the Cmc21 crystal phase, while the 2θ diffraction peaks corresponding to the Fm-3m crystal phase are at 30°±0.5° and 35°±0.5°.

[0050] Among them, the Cmc21 space group crystal phase belongs to the low-symmetry ordered structure. Its lattice distortion and local structure regulation can provide richer crystal interfaces and defect sites, which is conducive to improving the insertion / extraction process of active ions. At the same time, the Fm-3m space group crystal phase has high crystal symmetry and a relatively regular three-dimensional lattice structure, which is conducive to reducing lattice transport obstacles, thereby improving the ion transport capability inside the material.

[0051] The mass fractions of the Cmc21 and Fm-3m phases can be determined using X-ray diffraction combined with Rietveld full-spectrum fitting. For example, the sample is placed in a sealed sample holder, and Cu Kα rays are used to collect diffraction patterns. Based on the structural models of the Cmc21, Fm-3m, and other identifiable impurity phases, the background, peak shape, cell parameters, and scale factor are refined.

[0052] This invention optimizes Li a Q, Li₂O, TaCl₅, M b Q c The crystal structure described above is formed by adjusting the composition ratio and synergistically controlling the types of elements M and Q. A stable crystal phase structure enhances the structural stability of the material under high voltage and humid air environments, reduces the tendency for lattice decomposition, and thus improves the electrochemical and air stability of the material.

[0053] In one possible embodiment, as described above, the electrolyte material is rod-shaped particles with a diameter of 1-3 μm and a length of 5-20 μm.

[0054] This embodiment refers to the observation by scanning electron microscopy (SEM) showing that the halide electrolyte material exhibits a rod-shaped particle morphology with a diameter of 1-3 μm and a length of 5-20 μm. Its suitable particle size balances the contact area between particles and compaction performance. When pressing to form an electrolyte layer or preparing a composite cathode, this facilitates the construction of a continuous ion transport network and reduces interfacial impedance between particles. The rod-shaped particles can form overlapping transport paths, improving the continuity of particle connections and promoting lithium-ion transport.

[0055] In a second aspect, the present invention provides a method for preparing an electrolyte material according to any one of the first aspects of the present invention, comprising the following steps:

[0056] A raw material system including lithium source, tantalum source, M source and oxygen source is subjected to a first-stage annealing treatment to obtain a halide electrolyte precursor;

[0057] The halide electrolyte precursor is subjected to a two-stage annealing process to obtain the halide electrolyte material.

[0058] The first stage of annealing is performed at a temperature of 120-230℃ for 2-8 hours; the second stage of annealing is performed at a temperature of 230-260℃ for 3-10 hours.

[0059] In this invention, lithium source, tantalum source, M source, and oxygen source are first mixed according to the target composition ratio and then subjected to an annealing process. This stage is mainly used to promote the initial reaction and element diffusion between different raw materials, so that lithium, tantalum, M, and oxygen elements are uniformly distributed in the solid-phase system and form a halide electrolyte precursor with a certain structural basis.

[0060] The lithium source provides the lithium element needed to construct the lithium-ion transport network, the tantalum source participates in the construction of the halide framework as the main structural component, the M source is used to adjust the local crystal structure and chemical environment, and the oxygen source introduces oxygen element to regulate the stability of the crystal structure. Low-temperature pre-reaction avoids the abnormal grain growth or uneven element distribution caused by rapid reaction of raw materials under high-temperature conditions, which is beneficial to the subsequent formation of the target crystal phase.

[0061] Subsequently, the obtained halide electrolyte precursor was subjected to a two-stage annealing treatment to further promote element migration and crystal reconstruction within the precursor, allowing unreacted components to continue reacting and promoting the formation of a stable crystalline phase. By controlling the temperature and time of the two-stage annealing, the internal crystal structure of the material was gradually improved, reducing the generation of amorphous regions and impurity phases, and enhancing the stability of the crystal structure.

[0062] Meanwhile, during this stage, lithium-ion migration channels gradually form and are optimized, which is beneficial to improving the ion conduction performance of the material; the establishment of a stable crystal phase structure is also beneficial to improving the material's ability to maintain its structure under high voltage and humid air conditions.

[0063] This invention employs a two-stage annealing process: a low-temperature pre-reaction followed by high-temperature crystallization. This allows for the full diffusion of elements and their synergistic construction of the target halide electrolyte structure, resulting in a homogeneous and crystalline electrolyte material without the need for high-energy ball milling. Through the aforementioned process control, the obtained material exhibits high ionic conductivity, a wide electrochemical window, and good air stability, while also improving the controllability of the preparation process and its adaptability to large-scale production.

[0064] In one specific embodiment, the preparation process of the present invention can be realized using conventional solid-phase material preparation equipment. For example, the raw material mixing process can employ equipment such as a planetary mixer, drum mixer, V-type mixer, or three-dimensional mixer to fully mix and uniformly disperse the lithium source, tantalum source, M source, and oxygen source; the first-stage annealing treatment and the second-stage annealing treatment can be carried out using a tube furnace, box furnace, atmosphere furnace, or continuous sintering furnace, respectively, and the precursor formation and target electrolyte crystal phase transformation can be achieved by controlling the furnace temperature, holding time, and protective atmosphere.

[0065] The annealing equipment can be equipped with atmosphere control systems such as nitrogen, argon, oxygen, or ozone to regulate the reaction environment and improve the structural stability of the material. For large-scale production, continuous rotary kilns, roller kilns, or continuous pusher furnaces can be further adopted to achieve continuous feeding of raw materials, segmented heating, and continuous discharge, thereby improving production efficiency and reducing labor costs.

[0066] In one possible embodiment, as described above, an annealing process is performed in an inert gas atmosphere, which includes at least one of nitrogen and argon.

[0067] The two-stage annealing process is carried out in a mixed gas atmosphere, which includes at least one of nitrogen and argon, with the total volume fraction of argon and nitrogen being 90-95%, and the remainder being at least one of oxygen and ozone.

[0068] In this embodiment, an inert gas environment is used in the first annealing process, which can reduce the interference of external active components on the reaction system, avoid unexpected side reactions of raw materials during the pre-reaction process, and enable each component element to diffuse and combine according to a predetermined path.

[0069] In the two-stage annealing process, the inert gas in the mixed gas acts as the main component to maintain the stability of the halide crystal structure; a small amount of oxygen or ozone can provide an appropriate oxidizing environment, which is conducive to promoting the stable existence of oxygen in the crystal structure and lattice regulation, further optimizing the local coordination environment of the material, and improving the integrity of the crystal structure.

[0070] In one possible embodiment, as described above, the lithium source is at least one of LiCl, LiOH, Li2O, Li2O2, LiCl·H2O, Li2S, and Li3N.

[0071] In this embodiment, all of the above-mentioned lithium-containing compounds can provide lithium to the reaction system. Among them, lithium halides such as LiCl can directly provide lithium ions and a halogen environment; oxygen-containing lithium sources such as Li2O and Li2O2 can simultaneously supplement lithium and oxygen elements and participate in regulating the crystal structure and local coordination environment; components containing water of crystallization or hydroxyl groups such as LiOH and LiCl·H2O can undergo dehydration or structural transformation during annealing, which is beneficial to promoting the diffusion reaction between raw materials.

[0072] In one possible embodiment, as described above, the source M is at least one of AlCl3, GaCl3, WCl5, WCl6, NbCl5, and TaCl5.

[0073] In this embodiment, W and Nb are high-valence metal elements with strong coordination ability, which can adjust the halide lattice structure and improve the stability of the material structure; Al, Ga and other elements can adjust the local crystal environment and defect state, which is beneficial to optimizing the lithium ion migration path.

[0074] Two-stage annealing is preferably carried out in a closed or semi-closed corrosion-resistant container, such as a sealed quartz tube or a covered alumina crucible. The weighing, mixing and loading of raw materials are completed in an inert atmosphere, and the container is sealed after being purged with nitrogen or argon to reduce compositional deviations caused by volatilization.

[0075] In one possible embodiment, as described above, the oxygen source is at least one of Li2O, Li2O2, LiCl·H2O, AlCl3·6H2O, and Al(OH)3.

[0076] In this embodiment, oxygen-containing compounds such as Li₂O, Li₂O₂, LiCl·H₂O, AlCl₃·6H₂O, and Al(OH)₃ can provide oxygen to the system, enabling oxygen to participate in the construction of the oxyhalide crystal structure. Li₂O and Li₂O₂ can simultaneously provide lithium and oxygen, which is beneficial for compositional regulation; oxygen sources containing water of crystallization or hydroxyl groups release active oxygen components during annealing, promoting the bonding of oxygen with the main crystal lattice; and aluminum-containing oxygen sources can simultaneously introduce Al, achieving multi-element synergistic regulation.

[0077] The present invention can also introduce oxygen and ozone as oxygen sources in the two-stage annealing process to further regulate the elemental composition of the system.

[0078] In one possible embodiment, as described above, before the first stage of annealing, the raw material system is subjected to a first premixing treatment, and before the second stage of annealing, the halide electrolyte precursor is subjected to a second premixing treatment.

[0079] In this embodiment, a premixing process is performed before the annealing process. This process is mainly used to ensure that the lithium source, tantalum source, M source and oxygen source are uniformly dispersed at the microscale, so that each element can fully contact and undergo preliminary reaction during the low-temperature annealing process to form a uniformly composed halide electrolyte precursor.

[0080] After a period of annealing, a certain structural basis has been formed inside the precursor, but some incompletely reacted areas or local component distributions may still be different. Therefore, a premixing process is carried out again before the second annealing process to further break up the agglomerated areas, redisperse the precursor particles, improve the elemental uniformity in the subsequent crystal reconstruction process, and promote the formation of a stable target crystal phase.

[0081] In one specific implementation, the premixing process can be achieved by mechanical mixing, such as using a planetary mixer, a three-dimensional mixer, a V-type mixer, or a high-speed mixing device.

[0082] Thirdly, the present invention provides an electrolyte membrane comprising any electrolyte material according to any of the first aspects of the present invention, or an electrolyte material obtained by any of the methods according to the second aspect of the present invention.

[0083] The electrolyte membrane provided by the present invention is prepared from the above-mentioned halide electrolyte material. Since the electrolyte material has high ionic conductivity, wide electrochemical window and excellent air stability, the formed electrolyte membrane can provide a continuous transport channel for lithium ions, and at the same time, it serves as an isolation layer between the positive and negative electrodes to reduce the risk of electronic short circuit.

[0084] Among these advantages, higher ionic conductivity can reduce the migration resistance of lithium ions in the electrolyte membrane, reduce polarization during battery charging and discharging, and improve battery rate performance; a wider electrochemical window can reduce the risk of electrolyte membrane decomposition during high-voltage charging and discharging, making it compatible with high-voltage cathode materials and improving the battery's operating voltage range and energy density; and excellent air stability can reduce the environmental sensitivity of the electrolyte membrane during preparation, storage, and assembly, and improve the stability of the production process.

[0085] Electrolyte membranes can be obtained by performing film-forming treatment on the halide electrolyte material provided by this invention. For example, the prepared halide electrolyte powder can be dried and then subjected to cold pressing, hot pressing, or isostatic pressing under certain pressure conditions to allow the electrolyte particles to fully contact each other and form a dense structure, thereby obtaining a solid electrolyte membrane. Furthermore, the halide electrolyte material can be mixed with an appropriate amount of binder to prepare an electrolyte slurry, which can then be coated and dried to form a composite electrolyte membrane.

[0086] Fourthly, the present invention provides an electrode comprising any electrolyte material according to any of the first aspects of the present invention, or an electrolyte material obtained by any of the methods according to the second aspect of the present invention.

[0087] The electrode provided by this invention is a composite electrode containing a solid electrolyte, that is, a halide electrolyte material and an electrode active material are used together to form the electrode structure.

[0088] Because halide electrolytes possess high lithium-ion transport capabilities, their introduction into the electrode can fill the gaps between active material particles, constructing a continuous lithium-ion transport network within the electrode. This shortens the lithium-ion diffusion path, reduces the interfacial impedance between the active material and the electrolyte, and improves the utilization rate of the active material. Simultaneously, halide electrolytes have a wide electrochemical window, reducing the risk of electrolyte decomposition during high-voltage charge-discharge processes, improving electrode structural stability, and ultimately enhancing battery cycle performance.

[0089] Electrodes can be prepared by mixing halide electrolyte materials with positive electrode active materials, conductive agents, and binders. For example, halide electrolyte materials can be mixed with positive electrode active materials such as lithium nickel cobalt manganese oxide, lithium cobalt oxide, and lithium manganese iron phosphate, so that the electrolyte particles are uniformly dispersed between the active materials. Then, composite electrodes are prepared by processes such as dry pressing, roll forming, or wet coating. Through the above methods, the solid electrolyte and active materials can be fully contacted at the microscale, improving the lithium-ion transport efficiency inside the electrode.

[0090] Fifthly, the present invention provides a battery comprising the electrolyte membrane of the third aspect of the present invention, or the electrode sheet of the fourth aspect of the present invention.

[0091] The battery provided by this invention uses an electrolyte membrane and electrode prepared from the halide electrolyte material provided by this invention. Therefore, during the charging and discharging process of the battery, the high ionic conductivity can reduce the impedance in the lithium-ion transport process, improve the battery rate performance and charging and discharging efficiency; the wide electrochemical window can enable the battery to be adapted to higher voltage cathode materials, improve the battery operating voltage and energy density; and the excellent air stability can reduce the environmental control requirements in the battery manufacturing process, improve the battery production consistency and reliability.

[0092] A battery can be formed by sequentially assembling composite electrodes, an electrolyte membrane, and a negative electrode. For example, a composite positive electrode containing a halide electrolyte material, an electrolyte membrane, and a lithium metal negative electrode or other negative electrode materials can be stacked and assembled, followed by pressing, encapsulation, and formation treatment to obtain an all-solid-state battery. Because a solid-state electrolyte system is used, the risks of leakage, evaporation, and combustion associated with traditional liquid electrolytes are avoided, improving battery safety.

[0093] The specific battery structure, positive electrode material, negative electrode material, and auxiliary components provided in this invention are not limited and can be selected according to actual application requirements. For example, the positive electrode can be a lithium transition metal oxide positive electrode material, such as lithium cobalt oxide (LiCoO2), nickel-cobalt-manganese ternary material (NCM), nickel-cobalt-aluminum ternary material (NCA), lithium-rich manganese-based material, etc.; it can also be a phosphate system positive electrode material, such as lithium iron phosphate (LiFePO4), lithium manganese iron phosphate (LiMnFePO4), etc. The negative electrode can be a carbon-based negative electrode material, such as graphite, hard carbon, etc., or it can be a silicon-based negative electrode material, tin-based negative electrode material, or lithium metal negative electrode material, etc. Depending on different application scenarios, it can also be further matched with electrode systems such as sulfur-based positive electrode and lithium metal negative electrode in lithium-sulfur batteries.

[0094] In one possible embodiment, the battery is a solid-state battery, which includes a solid electrolyte layer. The solid electrolyte material in the solid electrolyte layer includes any electrolyte material according to the first aspect of the present invention, or an electrolyte material obtained by any method according to the second aspect of the present invention.

[0095] Since solid-state batteries do not contain a flowable liquid electrolyte, they rely on a solid electrolyte to simultaneously achieve lithium-ion transport and electrode isolation. Therefore, the electrolyte material is required to have high ionic conductivity, a wide electrochemical stability window, and good structural stability.

[0096] This invention utilizes the synergistic regulation of multiple elements, including Li, Ta, O, M, and Q, to construct a halide electrolyte system with a stable crystal structure, enabling the material to possess both high lithium-ion transport capacity and good electrochemical stability. It can simultaneously meet the application requirements of all-solid-state batteries for both the electrolyte layer and the composite electrode, and is particularly suitable for next-generation solid-state energy storage systems with high energy density, high safety, and long cycle life.

[0097] In one specific embodiment, the solid-state battery constructed using the halide electrolyte material of the present invention, in addition to including an electrolyte membrane and / or electrodes containing electrolyte material, may have other battery components selected according to actual application requirements.

[0098] For example, the positive electrode active material can be selected from layered oxide positive electrode materials, olivine-type positive electrode materials, spinel-type positive electrode materials or lithium-rich positive electrode materials, and the negative electrode material can be selected from lithium metal, lithium alloy, graphite, silicon-based negative electrode materials, silicon-carbon composite negative electrode materials, lithium titanate, etc.

[0099] In addition, solid-state batteries may also include conventional components such as current collectors, conductive agents, binders, and encapsulation structures. For example, the positive electrode current collector can be selected from aluminum foil, and the negative electrode current collector can be selected from copper foil; the conductive agent can be selected from conductive carbon black, graphene, carbon nanotubes, etc.; and the binder can be selected from polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), etc.

[0100] The solid electrolyte layer includes at least a main electrolyte layer formed by the halide electrolyte material of the present invention. The solid electrolyte layer can be a single layer or a composite multilayer structure. When lithium metal or lithium alloy anode is used, an interface protection layer can be set between the main electrolyte layer and the anode layer to reduce interface side reactions.

[0101] Sixthly, the present invention provides an electrical device including the battery of the fifth aspect of the present invention.

[0102] The electrical equipment provided in this invention uses an all-solid-state battery with high ionic conductivity, wide electrochemical window and excellent air stability as an energy supply device, thus achieving higher energy utilization efficiency, more stable power output and longer service life.

[0103] Specifically, in the field of new energy vehicles, the use of these batteries can improve vehicle range, enhance fast charging and discharging performance, and improve the safety of the power system; in the field of portable electronic devices, they can improve the continuous working time and high-load operation capability of the devices; and in the field of energy storage equipment, they can improve the long-term operational stability and cycle life of energy storage systems.

[0104] The electrical devices provided by this invention can include, but are not limited to, new energy vehicles, power tools, smartphones, laptops, drones, robots, home energy storage devices, and grid energy storage devices. By using the battery provided by this invention as a power supply module, these devices can meet the demands for high energy density, high safety, and long lifespan energy storage devices in various application scenarios.

[0105] The present invention will be described in more detail below through specific embodiments.

[0106] Example 1:

[0107] This embodiment is used to prepare the electrolyte material provided by the present invention.

[0108] The raw materials for the synthesis of halide electrolytes, Li₂O, TaCl₅, and LiF, were weighed into a mixer according to a stoichiometric ratio of 0.9LiF·0.1Li₂O·0.9TaCl₅·0.1TaCl₅. The mixing speed was 25,000 rpm, with each mixing cycle lasting 30 seconds and followed by a 10-minute interval, for a total of 6 cycles. A first-stage annealing treatment was then performed to obtain the precursor at 230℃ for 4 hours; followed by a second-stage annealing treatment at 260℃ for 6 hours.

[0109] Example 2-16

[0110] The experimental procedure was basically the same as in Example 1, except that the raw materials were added according to the stoichiometric ratios shown in Table 1.

[0111] Example 17:

[0112] This embodiment is used to prepare the electrolyte material provided by the present invention.

[0113] The raw materials for the synthesis of halide electrolytes, Li₂O, TaCl₅, LiF, and NbCl₅, were weighed into a mixer according to the stoichiometric ratio of 0.3LiF·0.7Li₂O·1.05TaCl₅·0.025NbCl₅. The mixing speed was 25,000 rpm, with each mixing cycle lasting 30 seconds and a 10-minute interval, for a total of 6 cycles. A first-stage annealing treatment was then performed to obtain the precursor at 230℃ for 4 hours; followed by a second-stage annealing treatment at 260℃ for 6 hours.

[0114] Examples 18-20

[0115] The experimental procedure was basically the same as in Example 17, except that the raw materials were added according to the stoichiometric ratios shown in Table 1.

[0116] Example 21:

[0117] This embodiment is used to prepare the electrolyte material provided by the present invention.

[0118] The raw materials for the synthesis of halide electrolytes, namely Li₂O, TaCl₅, LiF, NbCl₅, and GaCl₃, were weighed into a mixer according to the stoichiometric ratio of 0.3LiF·0.7Li₂O·1.05TaCl₅·0.025NbCl₅·0.025GaCl₃. The mixing speed was 25,000 rpm, with a mixing interval of 30 seconds and a 10-minute interval, for a total of 6 times. A first-stage annealing treatment was then performed to obtain the precursor at 230℃ for 4 hours; followed by a second-stage annealing treatment at 260℃ for 6 hours.

[0119] Example 22:

[0120] This embodiment is used to prepare the electrolyte material provided by the present invention.

[0121] The raw materials for the synthesis of halide electrolytes, namely Li₂O, TaCl₅, LiF, NbCl₅, and WCl₆, were weighed into a mixer according to the stoichiometric ratio of 0.3LiF·0.7Li₂O·1.05TaCl₅·0.025NbCl₅·0.025WCl₆. The mixing speed was 25,000 rpm, with a mixing interval of 30 seconds and a 10-minute interval, for a total of 6 times. A first-stage annealing treatment was then performed to obtain the precursor at 230℃ for 4 hours; followed by a second-stage annealing treatment at 260℃ for 6 hours.

[0122] Example 23:

[0123] This embodiment is used to prepare the electrolyte material provided by the present invention.

[0124] The raw materials for the synthesis of halide electrolytes, namely Li₂O, TaCl₅, LiF, NbCl₅, and AlCl₃, were weighed into a mixer according to the stoichiometric ratio of 0.3LiF·0.7Li₂O·1.05TaCl₅·0.025NbCl₅·0.025AlCl₃. The mixing speed was 25,000 rpm, with a mixing interval of 30 seconds and a 10-minute interval, for a total of 6 times. A first-stage annealing treatment was then performed to obtain the precursor at 230℃ for 4 hours; followed by a second-stage annealing treatment at 260℃ for 6 hours.

[0125] Comparative Example 1:

[0126] The electrolyte material is prepared as follows:

[0127] According to the stoichiometric ratio of LiF·TaCl5, the raw materials for the synthesis of halide electrolytes, LiF and TaCl5, were weighed into a mixer. The mixing speed was 25,000 rpm, with each mixing cycle lasting 30 seconds and a 10-minute interval, for a total of 6 cycles. A first-stage annealing treatment was then performed to obtain the precursor at 230℃ for 4 hours; followed by a second-stage annealing treatment at 260℃ for 6 hours.

[0128] Comparative Example 2:

[0129] The electrolyte material is prepared as follows:

[0130] The halide electrolyte synthesis raw materials Li₂O, TaCl₅, LiF, NbCl₅, and GaCl₃ were weighed into a mixer according to the stoichiometric ratio of 0.3LiF·0.7Li₂O·1.05TaCl₅·0.025NbCl₅·0.025GaCl₃. The mixing speed was 25000 rpm, with each mixing cycle lasting 30 seconds and followed by a 10-minute interval, for a total of 6 cycles. The resulting precursor was then subjected to an annealing treatment at 260℃ for 6 hours.

[0131] Test Example 1

[0132] The XRD diffraction mode used in this experiment is CuKα (λ=1.54178Å), with tube voltage and tube current of 40 kV and 40 mA, respectively. To avoid exposing the electrolyte to air, the XRD test range is 10°-80°, the scan rate is 5° / min, and the step size is 0.02°.

[0133] like Figure 1 The XRD comparison spectrum provided by the present invention is shown. Compared with Comparative Example 1, the impurity peaks corresponding to the changes in composition in Examples 9 and 21 are reduced. The main diffraction peaks of the electrolyte material prepared by the two-step annealing method are located in the XRD spectrum. The diffraction peaks of 2θ at approximately 14°±0.5°, 20°±0.5°, 25°±0.5°, 28.5°±0.5°, 31.5°±0.5°, 43°±0.5°, and 46.5°±0.5° correspond to the Cmc21 crystal phase, and the diffraction peaks at approximately 30°±0.5° and 35°±0.5° correspond to the Fm-3m crystal phase.

[0134] Test Example 2

[0135] This test employed scanning electron microscopy (SEM) to observe the microstructure of the prepared halide electrolyte materials. The samples were placed in the SEM chamber and observed under accelerating voltages of 5-15 kV to obtain information on particle size and microstructure.

[0136] like Figure 2 The image shown is a SEM spectrum provided in Embodiment 9 of the present invention. Figure 3 The image shown is a SEM spectrum provided in Embodiment 21 of the present invention. Figure 4 The image shown is a SEM image provided in Comparative Example 1 of the present invention. The electrolyte morphology in Comparative Example 1 is an irregular blocky morphology, while that in Examples 9 and 21 is a rod-shaped morphology.

[0137] Test Example 3

[0138] The solid electrolytes prepared in Examples 1-23 and Comparative Example 1 were subjected to ionic conductivity and air stability tests (exposed at -50°C dew point for 4 hours, and the retention rate of their ionic conductivity was tested).

[0139] The test was conducted in a low-humidity room with a dew point of -50°C to assess air stability, specifically including:

[0140] After the solid electrolyte was exposed to a low-humidity chamber with a dew point of -50°C for 4 hours, 150 mg of powder was weighed and placed in a battery mold (inner diameter 10 mm). A pressure of 400 MPa was applied, and the AC impedance was tested using an electrochemical workstation with an applied voltage of 10 mV applied in the frequency range of 1 Hz to 1 MHz. The ionic conductivity of the solid electrolyte after exposure was calculated.

[0141] In a battery mold with a diameter of 10 mm, a halide electrolyte (electrolyte of Examples 1-23 or Comparative Example 1) and Li were placed... 5.4 PS 4.4 Cl 1.6 The electrolyte is pressurized and molded at a pressure of 200 MPa in Li. 5.4 PS 4.4 Cl 1.6 A lithium foil was stacked on one side and pressurized to form a solid structure under 50 MPa pressure. Stainless steel current collectors were placed on the top and bottom of the stack. Linear scanning voltammetry was performed with a scanning range of 1.5–6.0 V and a scanning rate of 0.1 mV / s. The oxidation potential of the material was determined by intersecting the tangent line drawn from the oxidation peak of the test curve with the abscissa. The test results are shown in Table 2.

[0142] Test Example 4

[0143] The solid electrolytes obtained in the above embodiments and comparative examples were exposed for 4 hours and then added to the composite positive electrode to form a positive electrode layer. The corresponding electrolytes were used as the electrolyte layer, and lithium metal was used as the negative electrode to assemble an all-solid-state battery. Specifically:

[0144] (1) Preparation of the positive electrode:

[0145] A ternary cathode material, an electrolyte exposed for 4 hours, a conductive agent (VGCF), and a binder (PTFE) are mixed in a mass ratio of 70:30:2:0.5 to prepare a cathode film. The cathode film is then combined with stainless steel to form a cathode electrode sheet.

[0146] (2) Lithium metal is used as the negative electrode.

[0147] (3) Preparation of sulfide solid electrolyte membranes:

[0148] An electrolyte membrane is prepared by thoroughly mixing sulfide electrolyte and binder (PTFE) at a mass ratio of 100:0.5.

[0149] The electrochemical performance of the solid-state battery was tested, and the results are shown in Table 3. These include:

[0150] 1) First charge and discharge test: The solid-state battery was tested at 25℃ with a constant current of 0.1C for 1 cycle, with a voltage range of 2.7-4.3V.

[0151] 2) Long cycle test: The solid-state battery is subjected to 1000 cycles of constant current charge and discharge at 0.5C at 25℃, with a voltage range of 2.7-4.3V.

[0152]

[0153]

[0154]

[0155] (1) As shown in Table 1, the ionic conductivity of Examples 1-9 is higher than that of the comparative examples, with Example 7 having the highest ionic conductivity. After adjusting x, the ionic conductivity of the electrolyte shows a trend of first increasing and then decreasing, but the ionic conductivity is still higher than that of the comparative examples. Examples 10-16 show the changes in ionic conductivity after changing the y value. Examples 17-23 show the changes in ionic conductivity after different M values. b Q c The composition and z content of Examples 21-23 are higher than those of all Examples and Comparative Examples.

[0156] (2) As the x content gradually increases, the air stability of the electrolyte material decreases slightly. However, after 4 hours of exposure, the ionic conductivity of Example 21 is higher than that of all examples and comparative examples. As the value of x gradually increases, the oxidation resistance of the electrolyte material decreases slightly.

[0157] (3) As shown in Table 3, compared with Examples 1-9 and the comparative examples, Example 7 has the best overall electrochemical performance; compared with Examples 10-20, Example 17 has the best overall performance; among all examples, Example 21 has the best discharge specific capacity, rate performance and cycle performance.

[0158] via (1-x)Li a Q·xLi2O·yTaCl5·zM b Q c Optimize the proportions of x, y, and z, and the metal compound M. b Q c By studying various types of halide electrolytes, halide electrolyte materials with good air stability and a wide electrochemical window were prepared. The obtained electrolyte materials exhibit ionic conductivity ≥9 mS / cm, and retain ≥90% of their ionic conductivity after exposure at a dew point of -50℃ for 4 hours. They possess a wide electrochemical window, and when matched with ternary cathode materials, their electrochemical performance is significantly improved within the 2.7-4.3V voltage range. In the preferred embodiment, the capacity retention rate is ≥80% after 1000 cycles.

[0159] Finally, it should be noted that other embodiments of the invention will readily occur to those skilled in the art upon consideration of the specification and practice of the invention disclosed herein. This invention is intended to cover any variations, uses, or adaptations of the invention that follow the general principles of the invention and include common knowledge or customary techniques in the art not disclosed herein, and is not limited to the precise structures described above and shown in the accompanying drawings, and various modifications and changes can be made without departing from its scope. The scope of the invention is limited only by the appended claims.

Claims

1. A halide electrolyte material, characterized in that, include: (1-x)Li a Q·xLi2O·yTaCl5·zM b Q c ; among which, 0 <x≤1,0.9≤y≤1.2,0<z≤0.5,1≤a≤3,1≤b≤5,3≤c≤6; M is at least one of Ta, Nb, W, Al, and Ga, and Q is at least one of F, Cl, Br, I, S, and N.

2. The electrolyte material according to claim 1, characterized in that, It includes the Cmc21 crystal phase and the Fm-3m crystal phase, wherein the mass fraction of the Cmc21 crystal phase and the Fm-3m crystal phase is greater than 90% of all crystal phases.

3. The electrolyte material according to claim 1 or 2, characterized in that, The electrolyte material is rod-shaped particles with a diameter of 1-3 μm and a length of 5-20 μm.

4. A method for preparing the electrolyte material according to any one of claims 1-3, characterized in that, Includes the following steps: A raw material system including lithium source, tantalum source, M source and oxygen source is subjected to a first-stage annealing treatment to obtain a halide electrolyte precursor; The halide electrolyte precursor is subjected to a two-stage annealing process to obtain the halide electrolyte material. The first-stage annealing process is carried out at a temperature of 120-230℃ for 2-8 hours; the second-stage annealing process is carried out at a temperature of 230-260℃ for 3-10 hours.

5. The method according to claim 4, characterized in that, The first-stage annealing process is carried out in an inert gas atmosphere, which includes at least one of nitrogen and argon. The two-stage annealing process is carried out in a mixed gas atmosphere, which includes at least one of nitrogen and argon, and the total volume fraction of argon and nitrogen is 90-95%, with the remainder being at least one of oxygen and ozone.

6. The method according to claim 5, characterized in that, The lithium source is at least one selected from LiCl, LiOH, Li2O, Li2O2, LiCl·H2O, Li2S, and Li3N; and / or, The M source is at least one of AlCl3, GaCl3, WCl5, WCl6, NbCl5, and TaCl5, and / or the oxygen source is at least one of Li2O, Li2O2, LiCl·H2O, AlCl3·6H2O, and Al(OH)3.

7. The method according to claim 6, characterized in that, Before the first stage of annealing, the raw material system is subjected to a first premixing treatment, and before the second stage of annealing, the halide electrolyte precursor is subjected to a second premixing treatment.

8. An electrolyte membrane, characterized in that, Includes the electrolyte material according to any one of claims 1-3, or the electrolyte material obtained by the method according to any one of claims 4-7.

9. An electrode sheet, characterized in that, Includes the electrolyte material according to any one of claims 1-3, or the electrolyte material obtained by the method according to any one of claims 4-7.

10. A battery, characterized in that, Includes the electrolyte membrane of claim 8, or the electrode of claim 9.

11. The battery according to claim 10, characterized in that, The battery is a solid-state battery, which includes a solid electrolyte layer. The solid electrolyte material in the solid electrolyte layer includes the electrolyte material according to any one of claims 1-3, or the electrolyte material obtained by any one of claims 4-7.

12. An electrical appliance, characterized in that, Includes the battery described in claim 10 or 11.